HPLC CHARACTERIZATION OF PHARMACOLOGICALLY ACTIVE METABOLITES FROM CASSIA AUGUSTIFOLIA LEAF EXTRACT - Gautam, Khushbu; Roy, Vishwaprakash; Saraf, Ashish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Cassia angustifolia also referred to as senna makkai or cassia senna, is a plant native to Saudi Arabia, Egypt, and Yemen, and is widely cultivated in India. This medicinal herb has been traditionally utilized to address various ailments, including liver diseases, constipation, typhoid, and cholera. This investigation aimed to assess the in-vitro antimicrobial, antioxidant, and anticancer activities, as well as the phytochemical components, of both aqueous and organic extracts derived from the leaves of C. angustifolia. The antimicrobial activities of C. angustifolia aqueous and organic extracts (methanol, ethanol, acetone, ethyl acetate) were examined using the disk diffusion method. The bioactivity-guided screening of C. angustifolia extracts resulted in the isolation and identification of three flavonoids: quercimeritrin (1), scutellarein (2), and rutin (3), which are reported for the first time from this plant. Furthermore, extracts of C. angustifolia demonstrate the ability to impede microbial growth.